مدى رضا العملاء عن خدمات شركات التأمين الخاصة في محافظة اللاذقية - Naser, Gaidak (Latakia University Journal - Economic and Legal Sciences Series, 2019)
مدى رضا العملاء عن خدمات شركات التأمين الخاصة في محافظة اللاذقية "دراسة ميدانية" غيدق ناصر هدف البحث إلى تحديد مدى رضا العملاء عن الخدمات التي تقدمها شركات التأمين الخاصة في محافظة اللاذقية, والمتمثلة بـ: جودة الخدمة التأمينية, والتسعير, والترويج, والتوزيع, وتعامل الموظفين مع العملاء, والعمليات, والشكل الخارجي والداخلي للشركة, والرضا العام. اعتمد البحث على منهج المسح الإحصائي, وتكون مجتمع البحث من جميع عملاء فروع شركات التأمين الخاصة في محافظة اللاذقية, أما عينة البحث فهي عينة عشوائية من العملاء خلال فترة تطبيق البحث, حيث تمّ استقصاء آراء (200) عميل من عملاء هذه الشركات, وبلغ عدد الاستبانات الصالحة للتحليل (185) استبانة, وبنسبة استجابة بلغت (92.5%). توصل البحث إلى عدد من النتائج أهمها أنّ العملاء راضون وبدرجة كبيرة عن (جودة الخدمات التأمينية, وخدمات الترويج, وخدمات التوزيع, وتعامل الموظفين مع العملاء, والشكل الداخلي والخارجي للشركة)؛ المقدمة من قبل الشركات محل الدراسة وبدرجة متوسطة عن خدمات التسعير والعمليات. The objective of the research is to determine customer satisfaction with the services provided by private insurance companies in Lattakia Governorate: quality of service, pricing, promotion, distribution, employee handling with customers, operations, internal and external appearance of the company and general satisfaction. The research was based on the statistical survey approach. The research community consisted of all the customers of the branches of the private insurance companies in Lattakia Governorate. The sample of the research is a random sample of customers during the period of application of the research. The survey of the opinions of 200 customers of these companies, For analysis (185), the response rate was (92.5%). The research reached a number of results, the most important of which is that customers are satisfied to a great extent by (quality of insurance services, promotion services, distribution services, dealing with customers, internal and external form of the company); Provided by the companies under study and to a medium extent for pricing services and operations.